Longitudinal association of quality of life and health behaviors with service member readiness - Yunnuo Zhu; Sheila F. Castañeda; Isabel G. Jacobson; Crystal L. Lewis; Felicia R. Carey; Scott C. Roesch; Rudolph P. Rull (PLoS ONE, 2026)
Background This study aimed to assess whether self-reported physical and mental health-related quality of life (HRQOL) scores could be useful indicators of military health readiness. Methods Survey data and Department of Defense administrative and medical records from 51,589 active duty Millennium Cohort Study participants across four enrollment panels (2001, 2004, 2007, 2011) were examined at baseline and 3- to 5- year follow-up endpoints. Baseline measures included HRQOL measured by the Veterans RAND 12-Item Health Survey (VR-12) mental and physical component summary scores, health behaviors (e.g., smoking, insomnia symptoms), and demographic and military covariates. Readiness outcomes measured at follow-up included health care utilization, separation status, military satisfaction, lost workdays, and non-obese body mass index (BMI). Poisson regression models with a robust error variance were used to examine the prospective relationship between HRQOL and military readiness outcomes. Results HRQOL remained a significant predictor of all five readiness outcomes after adjustment for covariates and other health behaviors. Participants with baseline physical HRQOL scores in the highest 15th percentile were more likely to meet readiness metrics (e.g., increased odds of non-obese BMI, fewer annual lost workdays, less annual health care utilization, and a higher likelihood of remaining in service or completing their service term) compared with those in the middle 70th percentile. Scoring in the lowest 15th percentile for baseline physical or mental HRQOL was associated with being less likely to meet readiness metrics 3–5 years later. Conclusion Higher physical HRQOL may be a positive indicator of military readiness, while lower physical and mental HRQOL may signal impaired readiness. Assessment of HRQOL using the VR-12 is an easy, patient-centered tool that may help military leaders identify service members needing early interventions and improve readiness and retention.